An Analysis Of Linguistic Errors In Scientific Articles Of Indonesian Language Education Students - Reza Pahlevi Ginting (Publikasi Indonesia, 2024)
This study examines linguistic errors in scientific articles written by students from the Indonesian Language Education Study Program at Universitas Malikussaleh. The primary objective is to identify, categorize, and analyze common mistakes that compromise the clarity, coherence, and quality of student writing. Employing a descriptive qualitative approach, the research focuses on errors in morphology, syntax, spelling, and punctuation. The data comprises four student-authored scientific articles published in Jurnal Kande, selected through purposive sampling based on criteria such as academic supervision and thematic relevance to Indonesian language education. The analysis reveals recurring issues, including grammatical inaccuracies, improper sentence structures, misused terminology, and spelling and punctuation errors, which diminish the clarity of arguments and affect the credibility of students' scientific communication. By identifying error patterns through content analysis, the study provides insights into their causes and effects, contributing to the existing knowledge of linguistic error analysis. The findings offer practical recommendations for enhancing students' scientific writing skills, which are essential for academic success and future professional growth. In conclusion, this study emphasizes the need for targeted linguistic training and mentorship to improve the quality of scientific writing and highlights the importance of continuous support systems in academic settings to address persistent language errors. It advocates for the implementation of specialized educational strategies to enhance students' writing clarity, accuracy, and professionalism.